1996
DOI: 10.1016/0166-3542(95)00838-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between structural properties and affinity for herpes simplex virus type 1 thymidine kinase of bromine substituted 5-heteroaromatic 2′-deoxyuridines

Abstract: The crystal structures of 5-(5-furan-2-yl)-2'-deoxyuridine (II), 5-(5-bromofuran-2-yl)-2'-deoxyuridine (IV) and 5-(3-bromothien-2-yl)-2'-deoxyuridine (V) have been studied in order to explain the different affinity of the compounds for the herpes simplex virus type 1 (HSV-1) thymidine kinase. These compounds present a variable affinity according to the position of the heteroatom substituting the five-membered ring. An unfavourable substitution in the five-membered ring for interaction with the HSV-1 thymidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Crystal structures for 1 and 6 match previously published unit cell and space group data. 57,58 Crystallographic data (excluding structure factors) for compounds 1, 2, 6, 8 and 9 in this paper have been deposited with the Cambridge Crystallographic Data Centre as supplementary publication number CCDC 627723, 627722, 627725, 627724 and 632875 respectively. Copies of the data can be obtained, free of charge, on application to CCDC, 12 Union Road, Cambridge CB2 1EZ, UK, (fax: +44-(0)1223-336033 or e-mail: deposit@ccdc.cam.ac.uk).…”
Section: X-ray Structuresmentioning
confidence: 99%
“…Crystal structures for 1 and 6 match previously published unit cell and space group data. 57,58 Crystallographic data (excluding structure factors) for compounds 1, 2, 6, 8 and 9 in this paper have been deposited with the Cambridge Crystallographic Data Centre as supplementary publication number CCDC 627723, 627722, 627725, 627724 and 632875 respectively. Copies of the data can be obtained, free of charge, on application to CCDC, 12 Union Road, Cambridge CB2 1EZ, UK, (fax: +44-(0)1223-336033 or e-mail: deposit@ccdc.cam.ac.uk).…”
Section: X-ray Structuresmentioning
confidence: 99%
“…Clearly, there is a difference between both classes of molecules. Crystal structure analysis revealed that all compounds have a quasi-coplanar geometry between the five-membered heterocyclic ring and the uracil base (Figure ). Intramolecular interactions stabilize this coplanarity. Interestingly, in the 2-thienyl series of compounds, coplanarity is stabilized by an interaction between the O4 carbonyl group of the uracil base and the sulfur atom of the thiophene ring (Figure , structure A ).…”
Section: The Playersmentioning
confidence: 99%